ANALISIS POLISEMI VERBA DERU DALAM KALIMAT BAHASA JEPANG-NIHONGO NO BUNSHOU NI OKERU (DERU) NO TAGIGO NO BUNSEKI - khairannur, wilda (Jurnal Gramatika, 2013)
In Japanese, there are many words that have the same senses and meanings, if these words are translated into Indonesian, ambiguity happens. Yet, if we try to examine the use of each word further, they actually have a different application in a sentence. Word which has quite many meanings is called Polisemi (Tagigo). Most of the time, Japanese learners face such difficulties to translate or interpret the words which are Tagigo due to its relevance to other words that occasionally have more than one sense and meaning. Its relevance to other words in Japanese make the learner misinterpret a sentence if they do not comprehend it wholly. This research was done to fully describe the senses and meanings which belong to DERU by analyzing Japanese sentences.